Traditional knowledge associated with sociobiodiversity products: a look in defense of knowledge holders in the Middle Juruá territory, Amazonas, Brazil (Research, Society and Development, 2022)
The sustainable use of resources by populations through traditional knowledge finds in the Conservation Units - UCs of the sustainable use category, a place of refuge for sociocultural expressions. The present study aimed to reveal the use of traditional knowledge associated with species of flora and fauna by riverside communities in the Amazon from the identification of species used by residents of two communities in the Middle Juruá territory, analyzing the similarity of uses between communities and a flowchart of the process of consolidation of traditional knowledge by human populations was constructed. For this, semi-structured forms and open interviews were applied. As a result, 95 species of use and 112 uses were identified, distributed in 07 major categories, the most recurrent uses are in the cosmetic and medicinal category. There was a tendency to form groups among respondents from the same community, which can show that traditional knowledge is passed on more consistently with the closest coexistence, the medicinal category is the one with the most uses 76 in total representing 67, 85% of the total, followed by the cosmetic category with 11 uses (9.82) and food with 10 uses (8.92%). It is concluded that the region has a great potential for products and uses of sociobiodiversity and that traditional populations are responsible for the protection of natural and territorial resources through sustainable management based on traditional knowledge.